S78 Increased cd16bricd62ldimcd11b+subset of neutrophils in bronchoalveolar lavage from patients with interstitial lung disease. (15th November 2017) - Chong, DLW; Sahota, J; Booth, HL; Porter, JC
Abstract : Introduction: The Interstitial Lung Diseases (ILD) are a heterogeneous group of inflammatory and fibrotic diseases of the interstitium, with worst cases resulting in pulmonary fibrosis (PF). Increased neutrophils are found within the lung or bronchoalveolar lavage (BAL) in ILD and predict a poor prognosis. Neutrophil adhesion molecules, e.g., CD18/b2 integrins (LFA-1; CD11a, Mac-1; CD11b and CR3; CD11c) and L-Selectin (CD62L) regulate cellular recruitment and fibrosis in animal models of bleomycin-induced PF. Expression of the Fc receptor (CD16) is upregulated during neutrophil activation, whilst ICAM-1 (CD54) is a marker for neutrophil reverse-transmigration back across the endothelium. Study Aim: Investigate adhesion molecule expression profile of neutrophils in ILD patients compared to controls. Methods: BAL samples were collected from ILD and non-ILD patients undergoing bronchoscopy with informed consent. Adhesion molecule expression was studied via flow cytometry by staining cells with CD16, CD62L, CD11b, CD11c, CD11a, CD18 and CD54 antibodies. Results: Flow cytometric analysis of BAL showed significantly more neutrophils in ILD lavage express CD11b and CD18 compared to non-ILD controls (p=0.0016 and p=0.0211 respectively). No significant differences were found in CD11c or CD11a expression. Further analysis revealed ILD lavage contained a higher percentage of CD16 bri CD62L dim neutrophil subset expressing CD11b than non-ILD lavage controls (p<0.0001); a subset previously associated with a suppressive phenotype. 1 In addition, ICAM-1 expression was significantly down-regulated in ILD lavage neutrophils (p=0.0397) and this was also reflected in the CD16 bri CD62L dim neutrophil population (p=0.0445). Conclusions: From our preliminary study, we have observed an increased percentage of CD16 bri CD62L dim CD11b + subset of neutrophils in ILD lavage compared to controls. ILD lavage neutrophils express significantly less ICAM-1. This suggests that more neutrophils are entering and being retained within the lung in ILD. Further experiments will dissect whether ILD neutrophils have altered functions (such as NETosis, ROS production, adhesion or migration) to contribute to disease progression. Reference: Pillay J, Kamp VM, van Hoffen E, Visser T, Tak T, Lammers JW, et al . A subset of neutrophils in human systemic inflammation inhibits T cell responses through Mac-1. J Clin Invest 2012;122(1):327–36.